(untitled) (International Seven Journal of Health Research, 2023)
Bernard-Soulier syndrome is a rare inherited disease characterized by thrombocytopenia, presence of extremely large platelets and prolonged bleeding time. Objective: This paper aims to present an alternative management of surgical dental procedures in a female patient, faioderma, 27 years old, carrier of Bernard-Soulier syndrome. Case Description: On clinical examination and history, the patient reported a history of recurrent pericoronaritis associated with units 38 and 48, and a history of bleeding associated with menstruation. Imaging examination revealed impacted and impacted dental units. The treatment plan included exodontia of elements 18, 28, 38, and 48 under general anesthesia, transfusion of platelet concentrates (01U apheresis or 07U pool) two hours before surgery, fresh frozen plasma reserve in case of transoperative bleeding, and RBC concentrate reserve, according to the guidelines prescribed by the hematologist. At the moment, in a seven-month postoperative follow-up, the patient evolves without signs and symptoms of coagulation disorders associated with exodontia. Conclusion: Thus, it is essential that dental professionals are aware of the multidisciplinary management strategies for this group of patients in order to minimize postoperative complications.